Comparison of robustness, resilience and intrinsic capacity including prediction of long-term adverse health outcomes: The KORA-Age study - Michaela Rippl; Marie-Theres Huemer; Lars Schwettmann; Eva Grill; Annette Peters; Michael Drey; Barbara Thorand (The Journal of Nutrition, Health and Aging)
Background: Frailty, resilience and intrinsic capacity (IC) are concepts to evaluate older person`s health status, but no comparison of their associations with adverse health outcomes exists. We therefore aimed to assess which concept is most useful for determining long-term health of older adults. Methods: Analyses were based on the KORA (Cooperative Health Research in the Region of Augsburg)-Age study (n = 940, 65–93 years). Frailty was evaluated using the physical frailty-phenotype by Fried et al. For comparability to resilience and IC, we chose the protective concept of robustness instead of frailty in the present analysis. Resilience was measured by the 11-item resilience-scale. The IC-score was based on 4 domains (locomotion, cognition, vitality and psychiatric capacities). Associations with falls, disability, and hospitalization at 3-year and 7-year follow-up and with mortality were evaluated by multivariable adjusted logistic and Cox regression. Concept overlaps were illustrated by a Venn-diagram. Results: In the fully adjusted models, robustness showed significant inverse associations with most outcomes (3-year follow-up: OR (95%CI): disability 0.448 (0.300−0.668), 7-year follow-up: falls 0.477 (0.298−0.764), hospitalization 0.547 (0.349−0.856), and all-cause mortality 0.649 (0.460−0.915)) while resilience and IC showed significant inverse associations with disability only (e.g., 7-year-follow-up: resilience: 0.467 (0.304−0.716), IC: 0.510 (0.329−0.793)). 23% of the participants met the criteria for both robustness and IC while 22% met those for robustness and resilience. Conclusion: Robustness was the most useful concept, showing the strongest protective associations for most adverse health outcomes. IC and resilience showed their main strengths in capturing protective associations for disabilities. Robustness overlapped with resilience and IC, supporting the concept of mind-body-interaction.